Inner Ear Connexin Channels: Roles in Development and Maintenance of Cochlear Function - Mammano, Fabio (Cold Spring Harb Perspect Med, 2019)
Connexin 26 and connexin 30 are the prevailing isoforms in the epithelial and connective tissue gap junction systems of the developing and mature cochlea. The most frequently encountered variants of the genes that encode these connexins, which are transcriptionally coregulated, determine complete loss of protein function and are the predominant cause of prelingual hereditary deafness. Reducing connexin 26 expression by Cre/loxP recombination in the inner ear of adult mice results in a decreased endocochlear potential, increased hearing thresholds, and loss of >90% of outer hair cells, indicating that this connexin is essential for maintenance of cochlear function. In the developing cochlea, connexins are necessary for intercellular calcium signaling activity. Ribbon synapses and basolateral membrane currents fail to mature in inner hair cells of mice that are born with reduced connexin expression, even though hair cells do not express any connexin. In contrast, pannexin 1, an alternative mediator of intercellular signaling, is dispensable for hearing acquisition and auditory function.